2019
DOI: 10.20944/preprints201912.0321.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration, Application and Importance of Collaboration in Sustainable Project Management

Abstract: The need to consider sustainability has substantially increased the complexity of implementing construction and infrastructure projects and new management practices have emerged during the past decade to tackle the global sustainability challenges, where the engagement and coordination of broader competences from stakeholders throughout the supply chain is required. This new project management paradigm has been accompanied by greater attention to the concept of collaborative business arrangements, often called… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Finally, positive evidence was found for the effect of GTS (H3) and ECS (H4) on EP. These findings accord with empirical findings in the literature in contexts other than Pakistan (e.g., Larsson & Larsson, 2020; Li, Qiao, Cui, & Wang, 2020; Tachizawa, Gimenez, & Sierra, 2015). The positive association of GTS and ECS with EP highlights that the firms of Pakistan are achieving the goals of reducing pollution and wastage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, positive evidence was found for the effect of GTS (H3) and ECS (H4) on EP. These findings accord with empirical findings in the literature in contexts other than Pakistan (e.g., Larsson & Larsson, 2020; Li, Qiao, Cui, & Wang, 2020; Tachizawa, Gimenez, & Sierra, 2015). The positive association of GTS and ECS with EP highlights that the firms of Pakistan are achieving the goals of reducing pollution and wastage.…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Chin, Tatb, and Sulaimana (2015) found that environmental collaboration moderates the relationship between green supply chain management practice and sustainable performance. In summary, the existing literature confirms the significant relationships of GTS with EP and ECS with EP directly and indirectly (Larsson & Larsson, 2020; Li, Qiao, Cui, & Wang, 2020; Tachizawa et al, 2015); however, in the presence of IGI and PES, the association between GTS and ECS disappears. Thus, given the lack of evidence, we proposed the following hypotheses:H3 GTS has a positive and significant effect on EP.H4 ECS has a positive and significant effect on EP.…”
Section: Literature Review and Conceptualizationmentioning
confidence: 65%
See 1 more Smart Citation
“…Since C. Eastman and colleagues introduced the basics of BIM in the 1970s, it has come to be seen as an evolution of CAD design systems that provide a more 'intelligent' form of interoperable information. At the core of BIM technology is the promotion of data models involving information on buildings, infrastructure and thus as innovation, it plays a central part in the digital transformation of the infrastructure sector towards sustainable management practices [6,14]. BIM innovation therefore a↵ects the project organizational behavior, but it is at the same time a↵ected by the industry at large [11,27,28,46], thus introducing a processual character.…”
Section: The Processual Character Of Digital Transformation: Bim Innovationmentioning
confidence: 99%
“…Several infrastructure projects, including electric road systems [3] and expanding existing railways [4] have been initiated. These sustainability-oriented projects are generally multi-actor and leverage the economies of digitalization in terms of decision-making [5,6]. The adoption of digitalization is shaped by the infrastructure sector context, by the (fragmented) interaction patterns among its constituents [7,8].…”
Section: Introductionmentioning
confidence: 99%